Participatory Development of Textile Products of Ban Phu Thong Community, Sukhothai Province - Pantung, Pornchai (Area Based Development Research Journal, 2019)
This research aims to 1) develop woven products by community participation, and 2) raise the standard of community’s products. This research is a combination of qualitative and quantitative approaches. Two steps in developing the textile consist of textile pattern design and transfer of knowledge and skills in the textile production. The sample group is the 10 textile manufacturers in Ban Phu Thong community, Wang Nam Khao sub-district, Ban Dan Lan Hoi district, Sukhothai province. Three developed patterns reflect the community identity. The research findings reveal textile patterns inspired by the local items known to tourists visiting Ban Phu Thong. The emerged patterns that symbolize the local identity are included a mushroom, a 700-year-old teak, and a bat. The textile manufacturers have learned the guidelines in woven pattern design and dyeing techniques. The local manufacturers are able to form a group to establish a learning hub for textiles production to those interested. Additionally, their textile products have now registered upon OTOP Standard.